(untitled) (Proceedings of the International Conference of Geological Engineering Faculty, 2022)
Aspiring geopark of Krayan Highland (Kaltara) and Sangkulirang-Mangkalihat mountain range is a geoheritage located in Northeast Kalimantan. The diversity of its nongeological aspects is located at the forests with High Conservation Value. Based on its intrinsic value, geosite is grouped within geological hotspots into diverse value areas (geoarea), by compiling them into data of geodiversity, biodiversity, and culturediversity. This inventory establishes 16 geosite types that are possible in 10 geological frameworks: anthropogeny, sedimentology, paleontology, mineralogy, stratigraphy, igneous rocks, metamorphic rocks, structural geology, neotectonics, geomorphology, hydrology and hydrogeology, geochemistry, geothermal, economics, paleogeography, and geohistory. Some sites are worth extraordinary and amazing Sites of Special Scientific Interest (SSSIs) and Regionally Important Geological and Geomorphological Sites (RIGS). Several geoheritage sites hold valuable evidence of Cenozoic magmatism and obduction, atoll and modern carbonate landscape, as well as distinctive hydrological features. Scientific meaning is close to the true value of the potential aspect. Its’ geological and landscape structures affect cultural tradition and biodiversity, forcing them to adapt. The geoheritage sites of Kaltara and Sangkulirang-Mangkalihat are popular in local, regional and national as well as global tourism spot.